Renaissance inquisitors : Dominican inquisitors and inquisitorial districts in Northern Italy, 1474-1527 - Tavuzzi, Michael M. (Studies in the history of Christian traditions ;, 2007)
Based on archival research, this study casts light on the Inquisition in northern Italy during the Renaissance. It focuses on some representative inquisitors and their principal pursuits - the prosecution of heretics, especially Waldensians and Judaizers, and witch-hunting.